Implementation of Digital Finance in Supporting Financial System Transformation in The Digital Era (Barbershop Vip Gending): (Digital Finance Implementation to Support Financial System Transformation at Barbershop VIP Gending) - Widya Dwy Anggrain; Ahmad Sahidah (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of digital finance at Barbershop VIP Gending in support of financial system transformation in the digital age. Using a qualitative approach with a case study design, data were collected through in-depth interviews, direct observation, and documentation of the owner, employees, and customers selected through purposive sampling. Data analysis employed the Miles and Huberman interactive model through the stages of data reduction, data presentation, and drawing conclusions and verification, with triangulation of sources and techniques to ensure data validity. The research results indicate that Barbershop VIP Gending has adopted a hybrid digital payment system via Bank Jatim’s QRIS, e-wallets, and cash payments. Although digital infrastructure is available and staff are trained, cash transactions still dominate due to the business’s location in a rural area and the customer base, which consists primarily of students. The use of digital finance has proven to increase transaction speed, streamline automatic financial record-keeping, and promote a more modern and professional business image. The main obstacles faced include internet connectivity issues, input errors, and limitations in the features of the point-of-sale (POS) application. Overall, the integration of digital finance has connected the barbershop to the formal financial ecosystem and opened up potential access to financing as well as long-term business growth.